OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN NGADA (Studi Pada Sektor Pajak Dan Retribusi Daerah) - Yohanes Virgilius Rani; Laurensius P sayrani; I Putu Y.B Pradana (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the optimization of Regional Original Revenue (PAD) in Ngada Regency, East Nusa Tenggara, with a focus on the regional tax and retribution sector. Optimizing PAD is crucial for regional fiscal independence and sustainable development financing.Data were analyzed using data reduction, data display, and conclusion drawing techniques.The findings show that PAD optimization in Ngada Regency is influenced by several key factors. Tax system innovation through digitalization (V-Tax application) has improved efficiency and transparency, although its implementation remains uneven due to infrastructure and digital literacy limitations. A humanistic yet firm collection program has proven effective in increasing compliance, but requires more accurate performance data to measure its impact. Tariff policies based on local economic conditions and periodic adjustments need greater transparency and stronger involvement of business actors. Tax education and socialization should be broadened and tailored to the characteristics of local communities. Collaboration with third parties (banks, digital service providers) has facilitated payment, yet must be balanced with improved internet access in remote areas.The study concludes that optimizing PAD in Ngada Regency requires a comprehensive approach that includes strengthening digital infrastructure and improving public digital literacy; enhancing the capacity of Bapenda human resources through training and development; conducting regular evaluations of program and policy effectiveness; increasing transparency and public participation in policy formulation; and expanding cooperation with various stakeholders to reach all segments of society.